Pendidikan Kewargaan dan Kebangsaan terhadap WNI di Malaysia - Moch. Mubarok Muharam; Bambang Sigit Widodo; Nugroho Hari Purnomo; Machfud, Agus; Danang Tandyonoman; Dinar Rizky Listyaputri; Fitrie, Revienda Anita; Artono (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2025)
Globalization has made the meeting of values and cultures among nations unavoidable. This globalization has blurred national borders, allowing individuals to communicate with others around the world so easily that no country can restrain it. As a result, the exchange of values and cultures can be easily conducted. However, the problem is that often in the era of globalization, Western influences and cultural values more easily affect Eastern countries (including Indonesia). Conversely, values and cultures from the East do not easily influence Western countries. Besides spreading positive values, globalization can also lead to the spread of negative values among Indonesian citizens, such as individualism, hedonism, consumerism, and so on. Therefore, education and citizenship awareness are needed for Indonesian citizens (including those in Malaysia). Indonesian citizens (WNI) in Malaysia have the potential to lose their sense of identity as Indonesians, due not only to globalization but also because they are living in another country. By living long-term in a foreign country, WNI can have their Indonesian values eroded. Therefore, Community Service (PKM) by lecturers from Fisipol Unesa to Malaysia is needed as an effort to provide civic and national education to WNI in Malaysia. The results of this PKM found that after the activities, participants' understanding of nationalism increased, and their sense of pride in Indonesia was also enhanced.